Perencanaan dan Pengendalian Produksi Dalam Sistem Logistik (Pendekatan Berbasis Praktikum Laboratorium) - Ruswandi, Nanda; Herlina, Rohma; Suri, Faras Karningtia; Dianisa, Pramesti Adwinda; Sandi, Evelyn; Sukarno, Iwan; Liperda, Rahmad Inca; Lusiani, Mirna (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
The concept of Production Planning and Control is closely related to logistics activities, including in determining the production of a product. Production planning and control aims to get a complete picture of how to plan and control production in the industry of each company, so that all costs can be reduced. Production planning, Rough Cut Capacity Planning (RCCP), Material Requirement Planning (MRP), Capacity Requirement Planning (CRP), and Line Balancing are some of the steps that need to be done in providing an overview of the production planning and control system at the